2020
DOI: 10.1177/0361684320962561
|View full text |Cite
|
Sign up to set email alerts
|

Testing a Model of How a Sexual Assault Resistance Education Program for Women Reduces Sexual Assaults

Abstract: The Enhanced Assess, Acknowledge, Act (EAAA) program has been shown to reduce sexual assaults experienced by university students who identify as women. Prevention researchers emphasize testing theory-based mechanisms once positive outcomes related to effectiveness are established. We assessed the process by which EAAA’s positive outcomes are achieved in a sample of 857 first year university students. EAAA’s goals are to increase risk detection in social interactions, decrease obstacles to risk detection or res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 89 publications
(164 reference statements)
0
19
0
Order By: Relevance
“…This is consistent with the outcome evaluation that showed significant reductions in completed rape, attempted rape, and forced sexual contact (in addition to other types of sexual victimization) among program participants ( Senn et al, 2015 , 2017 ). It is important to note that 45% of the women providing these responses and evaluating the success of their resistance were survivors, providing further evidence of the generalization of program benefits for women with and without a history of sexual assault ( Senn et al, 2015 , 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the outcome evaluation that showed significant reductions in completed rape, attempted rape, and forced sexual contact (in addition to other types of sexual victimization) among program participants ( Senn et al, 2015 , 2017 ). It is important to note that 45% of the women providing these responses and evaluating the success of their resistance were survivors, providing further evidence of the generalization of program benefits for women with and without a history of sexual assault ( Senn et al, 2015 , 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Examining women’s accounts of the information and skills from EAAA they used not only identified which components of the program women integrated into their lives, but enhanced understanding of the mechanisms that made EAAA effective in reducing sexual victimization, rape myth acceptance and victim-blaming attitudes, and increasing self-defense self-efficacy and risk perception. Mediation analyses of EAAA showed that the program’s positive effects on situational risk perception and willingness to use forceful resistance (measured using a hypothetical scenario) combined with improvements in self-defense self-efficacy explain the reductions in attempted and completed rape following program participation ( Senn et al, 2021 ). The current study complements and extends these findings by documenting how women resisted subsequent sexual assault threat(s) and the types of situations that required women’s resistance (e.g., being approached at a bus stop, hanging out with a date, and dancing at the bar).…”
Section: Discussionmentioning
confidence: 99%
“…Some (but not all) research suggests that single gender approaches may be more effective in terms of prevention approaches (DeGue et al, 2014). Prevention interventions such as the Enhanced Assess, Acknowledge, Act program has shown efficacy in reducing completed rape among cisgender women, explicitly addresses sexual identity and is currently being validated with transgender women (Senn et al, 2021), whereas the Men’s Project addresses men in general (Foubert & Newberry, 2006), but includes information about same-sex sexual violence. These gender-based approaches may not be appropriate, however, for nonbinary individuals, and more research is needed to assess whether programming improves outcomes among transgender and cisgender sexual minority men as well as their cisgender heterosexual peers.…”
Section: Discussionmentioning
confidence: 99%
“…Further, it is not women's responsibility to stop sexual violence from happening to them. However, research suggests that sexual assault resistance interventions can reduce women's likelihood of victimization by empowering them to detect risks, resist attempts, and defend themselves against sexual aggression (Senn et al, 2020). Therefore, while women wait for cultural change to happen, they may wish to consider participating in some form of self-defense training, such as the Enhanced Access, Acknowledge, Act program, which has been shown to reduce women's likelihood of experiencing rape both at one and two year follow-up (Senn et al, 2015(Senn et al, , 2017.…”
Section: Practice Implicationsmentioning
confidence: 99%